Biochemical and mineral changes in leaves and roots of treated wastewater irrigated olive trees - Sdiri, Wiem; Toumi, Dhekra; Akremi, Houda; Hassani, Rym; Ben Mansour, Hedi (New Zealand journal of crop and horticultural science, 2025)
The treated wastewater (TWW) is seen as a potential alternative for crop irrigation in areas with limited freshwater resources. This alternative water source may present a fertilising effect for plants and soils. The present study aims to assess young olive trees' physiological and biochemical behaviour as a result of dairy TWW irrigation. Therefore, olive tree parts are analysed following irrigation. Moreover, the two irrigation systems' efficiency is studied in the present work. Olea europaea L. cv. Chemlali leaves and roots were sampled from young olive trees irrigated for 12 months with TWW using surface drip irrigation (SDI) or manual irrigation (MI) systems. Treated wastewater seemed to improve significantly mineral amounts, especially Mg, K and Ca in olive leaves and roots. Moreover, this practice leads to ameliorating plant physiological performance by improving chlorophyll synthesis. These positive effects were observed following the SDI system application. On the other hand, the MI system promoted heavy metal translocation to plant roots and leaves. This phenomenon was blocked by the SDI system. The present results highlight that TWW seems to be an interesting bio-fertiliser of young Olea europaea L. cv. Chemlali trees.